Permanent Education in Health in the construction of senses and meanings about the Family Health Strategy: an experience report (Research, Society and Development, 2022)
Objective: to report the experience of a Permanent Education in Health workshop, which aimed at building meanings and meanings about the Family Health Strategy, based on the understanding presented by family health team workers and managers of the municipal health department. Methods: qualitative, descriptive study of the experience report type, which took place in a municipality in Bahia. It involved 39 participants, who were divided into 2 groups. The workshop took place on November 8 and 19, 2021, accounting for 4 hours for each group. It was organized in five moments that involved the construction of interactive panels and discussions on the theme. Results: By experiencing these moments, it was possible to perceive commitment on the part of the participants; at the same time that they brought with them different feelings that revolved around expectations about the workshop as well as of a personal nature; with regard to the senses and meanings, it was possible to approximate with teamwork, reception, continued care, prevention and health promotion and thus realize that their understandings shared with the National Policy of Primary Care. Conclusion: The workshop made it possible to perceive the relevance of Permanent Education in Health as a healthy way to strengthen the SUS, and the need to re-signify health work based on the meanings and meanings about the Family Health Strategy.